Antara Zakat Produktif Dan Konsumtif Bagi Peningkatan Pendapatan Masyarakat Muslim - Dewi, Komala; Ritonga, Mirwansyah Putra; Hutauruk, Fauziahnur (Jurnal Riset Akuntansi dan Bisnis, 2025)
The problem of poverty is also one of the political problems, because an important factor that is the concentration of the political world is the problem of the economy. Where the economy is one of three problems (poverty, stupidity and also disease), which must be addressed by the government to resolve the crisis in society. The method of writing this article is based on a literature review by conducting an in-depth review of books, interpretations and writings on zakat, consumptive and productive zakat and those related to it. The purpose of this writing is to find out the target to be achieved through this productive effort for mustahiq is an increase in the standard of living of mustahiq, especially in terms of socio-economics. The results of this research and discussion confirm that focusing on the shift from consumptive zakat to productive zakat, which allows mustahik to be more economically independent through the provision of business capital and skills training. With good management, consumptive zakat can be an integral part of an inclusive and sustainable development strategy in Indonesia